The Mixed Finite Element Method Based on the Crank-Nicolson Scheme for Darcy Flows in Porous Media - Poonepalle, Akshaya; Shi, Brent; Kang, Elly; Chin, Joseph; Singh, Mannan; Gupta, Prakhar; Malhotra, Riya; Kadiyala, Sanjana; Thadiparthi, Sirihansika; Kieu, Thinh; Kim, Yeeun (The PUMP Journal of Undergraduate Research, 2023)
This article is devoted to the a priori error estimates of the fully discrete Crank-Nicolson approximation for the Darcy flows. Optimal order error estimates in two different norms are established for the lowest order. Numerical experiments confirm the theoretical analysis regarding convergence rates.